Alternative Cropping Systems with Limited Irrigation - A. Schlegel (Kansas Agricultural Experiment Station Research Reports, 2018)
A limited irrigation study involving four cropping systems and evaluating four crop rotations was initiated at the Southwest Research-Extension Center near Tribune, KS, in 2012. The cropping systems were two annual systems (continuous corn [C-C] and continuous grain sorghum [GS-GS]) and two 2-year systems (corn- grain sorghum [C-GS]) and corn-winter wheat [C-W]). In 2017, corn yields were greatest in the corn-wheat rotation and least with continuous corn. Grain sorghum yields were greater following sorghum than following corn. The wheat was destroyed by a severe infestation of wheat streak mosaic virus and not harvested.
Keywords: alternative cropping systems; limited irrigation; southwest Kansas irrigation